English liberalism in Catalonia at the beginning of the nineteenth century: Manuel Casamada i Comella - Roviró Alemany, Ignasi (Journal of Catalan Intellectual History, 2013)
At the beginning of the nineteenth century, the literati and writers of the Spanish capital were divided in conservative and progressive factions and this ideological polarization was reflected in the literature. While the conservatives adopted the French aesthete Charles Batteux’s Principes de la littérature (1774), the more progressive thinkers modelled their production on Scottish minister Hugh Blair’s Lectures on Rhetoric and Belles Lettres (1783). Their use of Blair’s treatise reflects one way in which liberal English thought was being introduced in Spain and it also helped to more widely disseminate the ideas contained in Edmund Burke’s A Philosophical Enquiry into the Origin of Our Ideas of the Sublime and Beautiful (1757), a work of particular interest because it re-examined what had hitherto been regarded as two inseparable concepts. In Catalonia, Hugh Blair’s influence is seen in the writings of the liberal friar Manuel Casamada (1772–1841) and in the unpublished speech Casamada delivered at the Royal Academy of Belles Lettres of Barcelona in 1837. key words: Hugh Blair, Manuel Casamada, the beautiful, the sublime, Catalan aesthetics.